Sulforaphane-induced apoptosis involves p53 and p38 in melanoma cells - Rudolf, K; Cervinka, M; Rudolf, E (Apoptosis, 2014)
In malignant melanoma complex reprogramming of cell death and survival pathways leads to increased chemoresistance and poor longer-term survival. Sulforaphane (SF) is a promising isothiocyanate compound occurring in cruciferous plants with reported antiproliferative and proapoptotic activity in several tumor cell lines including melanoma. In this work we investigated the effects of SF in several melanoma cell lines and fresh melanoma cultivates. We found that SF is cytotoxic and induces mitochondrial, caspase-dependent apoptosis in our study model, however with lower efficiency in fresh melanoma cultivates. Moreover, our results indicate that in melanoma cell lines and fresh melanoma cultivates SF induces multiple signaling including oxidative stress-mediated activation of DNA-damage response pathway, changes in p38 kinase activity and enhanced expression of Bax and Puma proapoptotic proteins. In addition, in SF-exposed p53-mutant melanoma cells Puma expression seem to be under p38 control and acts as a compensatory proapoptotic mechanism. Conversely, decreased apoptosis in SF-exposed melanoma cultivates might be attributed to Akt-mediated suppression of p38 as well as p53 activity. Together, our results suggest that SF inhibits growth and proliferation and induces mitochondrial apoptosis both in melanoma cell lines as well as in fresh melanoma cultivates. This proapoptotic effect might be enhanced in combination with Akt inhibitors, in particular in melanoma samples. SF is thus commendable for further preclinical testing, both as a single agent as well as in combination regimens.
Keywords: Apoptosis; reaktivní formy kyslíku; signální transdukce; Anticarcinogenic Agents; Isothiocyanates; Skin Neoplasms; Humans; lidé; Mitochondria; mitogenem aktivované proteinkinasy p38; nádory kůže; sulfoxidy; Sulfoxides; Tumor Suppressor Protein p53; Caspases; kaspasy; mitochondrie; isothiokyanatany; Melanoma; melanom; Reactive Oxygen Species; Cell Line, Tumor; nádorové buněčné linie; nádorový supresorový protein p53; Signal Transduction; antikarcinogenní látky; apoptóza; p38 Mitogen-Activated Protein Kinases